2002
DOI: 10.1002/1099-0690(200211)2002:21<3507::aid-ejoc3507>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of C2-Symmetric Bis(sulfoxides): A New Approach in Asymmetric Synthesis

Abstract: Keywords: Asymmetric synthesis / Chiral acyl anions / Ligand design / Bis(sulfoxides)The preparation of various racemic or enantiopure C 2 -symmetric bis(sulfoxides) has been developed over the last decades. Numerous applications in organic synthesis (anionic condensation, cycloadditions) as well as in coordination chemistry have been worked out.[a] Université P. et M. Curie, UMR 7611, MICROREVIEWS: This feature introduces the readers to the authors' research through a concise overview of the selected topic. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 85 publications
(119 reference statements)
0
22
0
Order By: Relevance
“…In acyclic series with (S,S)-8, Solladié et al [82] and we [9] have found good yields and diastereoselectivities with aro- [83] we have proposed the model displayed in Scheme 20. The most favourable approach involves chelated transition state 74 in which nonbonding interactions between the p-tolyl group of the anion of 8, and the R group of the aldehyde Scheme 19 are minimised (compared to 75).…”
Section: Ii4 Condensation Onto Carbonyl Derivativesmentioning
confidence: 81%
See 2 more Smart Citations
“…In acyclic series with (S,S)-8, Solladié et al [82] and we [9] have found good yields and diastereoselectivities with aro- [83] we have proposed the model displayed in Scheme 20. The most favourable approach involves chelated transition state 74 in which nonbonding interactions between the p-tolyl group of the anion of 8, and the R group of the aldehyde Scheme 19 are minimised (compared to 75).…”
Section: Ii4 Condensation Onto Carbonyl Derivativesmentioning
confidence: 81%
“…This was first accomplished by Aggarwal et al using a water-soluble DCC variant reagent (morpho CDI 82) to transform the formaldehyde-alkylated bis(sulfoxide) 81 into methylenebis(sulfoxide) 83 (Scheme 22). [9] Another report by Carretero et al [87] mentions the synthesis of the (S,S)-1,1-bis(ethoxycarbonyl)-2,2-bis(p-tolylsulfinyl)ethene (86), in a two-step sequence involving first a quantitative condensation with oxomalonate, followed by a dehydration of 85 with DEAD. [9] Another report by Carretero et al [87] mentions the synthesis of the (S,S)-1,1-bis(ethoxycarbonyl)-2,2-bis(p-tolylsulfinyl)ethene (86), in a two-step sequence involving first a quantitative condensation with oxomalonate, followed by a dehydration of 85 with DEAD.…”
Section: Ii5 Preparation Of Alkylidenebis(sulfinyl) Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…[5a] All of these methods are among the most powerful and innovative approaches, but they usually lead to functionalized cyclopropanes. [12f] Alkylidene bis(p-tolylsulfoxides) [12] (3) were recently used as highly versatile partners for asymmetric syntheses [13] in the context of radical chemistry, [14] polar Michael additions, [15] and the Michael-initiated ring closure reaction which is used herein as the key step for the preparation of cyclopropane 2. [10] These reactions were restricted to aryl-and vinyl-substituted [10] cyclopropanes.…”
mentioning
confidence: 99%
“…To develop an even more general approach to the preparation of enantiomerically pure polyalkylated cyclopropanes (1; R, R 1 , R 2 = alkyl groups), we envisaged subjecting 2 to a combination of two consecutive selective sulfoxide/lithium exchanges, [12] a transmetalation reaction, and then a reaction with an electrophile (Scheme 1). [12f] Alkylidene bis(p-tolylsulfoxides) [12] (3) were recently used as highly versatile partners for asymmetric syntheses [13] in the context of radical chemistry, [14] polar Michael additions, [15] and the Michael-initiated ring closure reaction which is used herein as the key step for the preparation of cyclopropane 2. [12f] Alkylidene bis(p-tolylsulfoxides) [12] (3) were recently used as highly versatile partners for asymmetric syntheses [13] in the context of radical chemistry, [14] polar Michael additions, [15] and the Michael-initiated ring closure reaction which is used herein as the key step for the preparation of cyclopropane 2.…”
mentioning
confidence: 99%